Legality And Legal Certainty Of Ulayat Land For Indigenous Law Communities (Analysis of Decision Number 1430 K/Pdt/2022) - Edy Nurcahyo; Hudali Mukti; Ahmad Rosidi; Yogi Yasa Wedha; Ayu Putu Laksmi Danyathi (Jurnal Hukum Volkgeist, 2022)
Land disputes in Indonesia are still very high, including land disputes that occur on ulayat lands. In the settlement of land disputes in court, sometimes indigenous peoples have to lose in defending their rights due to the weakness of the legality factor of land ownership rights on ulayat land. To minimize customary land disputes, regulations are needed that guarantee legal protection and certainty for the customary lands of indigenous peoples. The research method used is normative legal research. In this study using a statutory approach. The analysis used is descriptive qualitative analysis. The ulayat land of the customary law community unit has received recognition regarding its existence as long as the fact is that it still exists. The acknowledgment of this existence has been stated in Article 3 of the Basic Agrarian Law, but in the implementing regulations there is still a legal vacuum that results in weak aspects of protection and legal certainty for the existence of ulayat land. The existence of customary law institutions that do not yet have legality becomes a barrier for customary law community units in defending their rights in ulayat land disputes. The existence of ulayat lands cannot be separated from the recognition of customary law communities who are part of the existence of ulayat lands. Legal certainty in providing protection for ulayat lands of customary law community units is very necessary to maintain the existence of ulayat lands.